2014
DOI: 10.1155/2014/917834
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Effects of Deer in Boreal Forest Ecosystems

Abstract: Many deer populations have recently increased worldwide leading to strong direct and indirect ecological and socioeconomical impacts on the composition, dynamic, and functions of forest ecosystems. Deer directly modify the composition and structure of vegetation communities, but they also indirectly affect other species of the ecosystem by modifying the structure of the vegetation. Here we review the results of a research program on overabundant white-tailed deer (Odocoileus virginianus) in the boreal forest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 99 publications
(136 reference statements)
1
25
0
Order By: Relevance
“…Our findings corroborate the view that deer herbivory is functionally a chronic disturbance agent, especially at high densities [64,65]. This chronic disturbance caused by severe herbivory would negatively impact native shrubs and herbaceous species with high palatability, but would benefit graminoids and ferns that had both low palatability and a growing point at or near ground level, and also benefit invasive species such as barberry that have low palatability because of high alkaloid concentrations [66].…”
Section: Deer Herbivorysupporting
confidence: 83%
“…Our findings corroborate the view that deer herbivory is functionally a chronic disturbance agent, especially at high densities [64,65]. This chronic disturbance caused by severe herbivory would negatively impact native shrubs and herbaceous species with high palatability, but would benefit graminoids and ferns that had both low palatability and a growing point at or near ground level, and also benefit invasive species such as barberry that have low palatability because of high alkaloid concentrations [66].…”
Section: Deer Herbivorysupporting
confidence: 83%
“…Experimental trials of animals in captivity or exclusion experiments have found evidence for both increasing and decreasing diversity in natural communities (Augustine and McNaughton 1998; Côté et al 2014; Kalisz et al 2014); which suggests that herbivory may indeed be inconsistent in its effects.…”
Section: Discussionmentioning
confidence: 99%
“…), and deciphering indirect effects of herbivore consumers is a very active field of research (see reviews in Rooney & Waller ; Côté et al . ). Herbivores influence feedbacks between plant and soil ecosystems, with resulting effects on plant succession depending on feeding preferences of grazers or browsers.…”
Section: Introductionmentioning
confidence: 97%